2014
DOI: 10.1038/bjc.2014.117
|View full text |Cite
|
Sign up to set email alerts
|

CD74: a new prognostic factor for patients with malignant pleural mesothelioma

Abstract: Background:The pro-inflammatory cytokine migration inhibitory factor (MIF) and its receptor CD74 have been proposed as possible therapeutic targets in several cancers. We studied the expression of MIF and CD74 together with calretinin in specimens of malignant pleural mesothelioma (MPM), correlating their expression levels with clinico-pathologic parameters, in particular overall survival (OS).Methods:Migration inhibitory factor, CD74, and calretinin immunoreactivity were investigated in a tissue microarray of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 53 publications
4
22
1
1
Order By: Relevance
“…Irrespective of the mechanism(s) involved, CD74 now meets the criteria as a validated marker of improved prognosis in stage III melanoma patients. Similar findings that high expression of CD74 is an independent prognostic factor for OS were recently reported in mesothelioma (27). …”
Section: Discussionsupporting
confidence: 90%
“…Irrespective of the mechanism(s) involved, CD74 now meets the criteria as a validated marker of improved prognosis in stage III melanoma patients. Similar findings that high expression of CD74 is an independent prognostic factor for OS were recently reported in mesothelioma (27). …”
Section: Discussionsupporting
confidence: 90%
“…CD74, a transmembrane glycoprotein, associates with the major histocompatibility complex (MHC) Class II and plays important roles in the intratumoral immune response [2729]. CD74 was overexpressed in thyroid malignancy, malignant pleural mesothelioma, and head and neck squamous cell carcinomas, and it is associated with advanced tumor stage [3032]. Shakib et al [33] found that both CD44 and CD74 proteins were significantly overexpressed in oral squamous cell carcinoma (OSCC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin, a Ca 2+ binding protein, is a diagnostic and prognostic marker for mesothelioma (Kao et al, 2011; Linton et al, 2014; Ordóñez, 2014; Otterstrom et al, 2014). So far, molecular mechanisms driving calretinin expression in mesothelioma remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%